REGULATORY IMPACT ASSESTMENT TERHADAP PENGATURAN PENGGUNAAN ARTIFICIAL INTELLIGENCE PADA JASA KEUANGAN PERBANKAN - Dewantara, Reka (Faculty of Law, Tanjungpura University, 2020)
The use of technology in bank services including the use of artificial intelligence makes bank services promise fast and efficient processes. Included in the funding products by banks are competitive by prioritizing digitalization and inclusiveness, but the development of regulations by the banking authorities has not facilitated the development of IT. This article aims to conduct regulatory impact assetsment on regulations related to the use of artificial intelligence in bank services in Indonesia through market conduct. The research in this article uses the type of normative legal research that is legal research conducted by examining library materials or also called library research. The results of the study show that in addition to the regulations of the FSA there are contract laws that provide the basis for banks to use artificial intelligence in their service services as a basis for conducting services operationally, the use of artificial intelligence in bank services must continue to pay attention to the principles of prudence and protection for consumers including in terms of their funds and personal data, prevention of money laundering and financial terrorism, and financial system stability through market conduct.Penggunaan teknologi pada jasa layanan bank termasuk penggunaan artificial intelligence membuat layanan bank menjanjikan proses cepat dan efisien. Termasuk pada produk-produk pendanaan oleh bank bersifat kompetitif dengan mengedepankan digitalisasi dan inklusif, namun perkembangan pengaturan oleh otoritas perbankan belum mewadahi perkembangan IT tersebut. Artikel ini bertujuan melakukan regulatory impact assetsment terhadap pengaturan terkait penggunaan artificial intelligence pada jasa layanan bank di Indonesia melalui market conduct. Penelitian dalam artikel ini menggunakan Jenis Penelitian hukum normatif yaitu penelitian hukum yang dilakukan dengan meneliti bahan pustaka atau disebut juga library research.Hasil peneltian menunjukkan bahwa di samping regulasi dari OJK terdapat hukum kontrak yang memberikan landasan untuk perbankan menggunakan artificial intelligence pada jasa layananya sebagai dasar melakukan operasionalnya, Penggunaan artificial intelligence pada jasa layanan bank harus tetap mmperhatikan prinsip kehati-hatian dan perlindungan bagi konsumen termasuk dalam hal dana dan data pribadi mereka, pencegahan tindak pidana pencucian uang dan terorisme, dan stabilitas sistem keuangan melalui market conduct.